Design and synthesis of dalbergin analogues and evaluation of anti-osteoporotic activity. Issue 8 (15th April 2017) - Kumar, Padam; Kushwaha, Priyanka; Ahmad, Naseer; Maurya, Saransh Wales; Dev, Kapil; Khedgikar, Vikram; Siddiqui, Ibadur Rahman; Trivedi, Ritu; Maurya, Rakesh
Graphical abstract: Abstract: The chemical modifications of the hydroxyl group of dalbergin have been described via the introduction of cyclic amine, ester and amide groups. Among the twenty-three prepared novel analogues of dalbergin, compound4d (EC50 2.3 μM) showed significantly increased proliferation as assessed by alkaline phosphatase activity and mineralization in calvarial osteoblast cells in vitro . Compound4d, at a dose of 1.0 mg/kg body weight exhibited the significant osteoprotective effect. It showed a significant increase in osteogenic gene expression RunX2 (∼4fold), ALP (∼5fold), OCN (∼4fold) and COL1 (∼4fold) as compared to control group at the same dose in vivo assay.